FREQUENCY OF DIABETICS IN ASTEROID HYALOSIS PATIENTS - Akram, Amjad; Niazi, M. Khizar; Ishaq, Mazhar; Azad, Nadia (Journal of Ayub Medical College Abbottabad, 2003)
Background: Asteroid hyalosis is a benign condition characterized by small white or yellow-white spherical opacities throughout the vitreous. The aetiology of this disorder is not clearly understood. Association of asteroid hyalosis with diabetes mellitus has been a debatable issue in ophthalmology. This study was carried out to determine the relationship between asteroid hyalosis and diabetes. Methods: The study was carried out in the Department of Ophthalmology, Military Hospital, Rawalpindi. Cases were picked up during routine eye examination that showed evidence of asteroid hyalosis. All patients of diabetes scheduled for routine follow-ups were also checked for active signs of diabetes. Fasting and two-hour postprandial blood glucose were checked and the frequency of diabetes mellitus in patients with asteroid hyalosis was determined. Results: Ninety-six cases of asteroid hyalosis were included. The median age of presentation was 55.68 years (range 40-71). It was bilateral in thirty-six cases. Twenty-eight cases were positive for diabetes. Conclusion: The association between asteroid hyalosis and diabetes appears to be significant. Patients found to be having the findings of asteroid hyalosis should be screened for diabetes. KEYWORDS: Asteroid Hyalosis; Diabetes Mellitus; Vitreous